Information Technology Ability Factors on Educator Performance that Have an Impact on the Quality of Learning in Equality Education (Lembaran Ilmu Kependidikan, 2023)
Technological advances will have an impact on changes in human civilization and culture. In the world of ICT implementation of the organizer's policy, the ICT impact is sometimes influenced by the impact of technological advances, the demands of the times, changes in culture and human behavior.  The purpose of the study is the influence of social factors in the use of information and communication technology (ICT) on the performance of educators, to determine the influence of task suitability factors in the use of information and communication technology (ICT) on the performance of educators, to determine the influence of long-term consequences in the use of information and communication technology (ICT) on the performance of educators , to find out the influence of the Affect factor in the use of information and communication technology (ICT) on the performance of educators, to find out the influence of complexity factors in the use of information and communication technology (ICT) on the performance of educators, to find out the influence of  educator performance  on the quality of learning.  This study uses a quantitative descriptive approach by knowing how much influence each variable dimension of social factors, dimensions of task suitability factors, dimensions of long-term consequences factors, dimensions of affect factors, and dimensions of complexity factors. Tests carried out Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, Normality Test.  The results of the research data that have been analyzed with Part Least Square (PLS), show that: (1) The percentage of ICT ability factor to communication is 0.042 or 4.2% this shows that the greater the ICT ability educators will be able to improve communication by 4.2%.  (2) The amount of ICT capability factor for educator performance is 0.031 or 3.1%. This shows that the greater the ability of ICT capabilities will be able to improve the performance of educators by 3.1%.  (3) The amount of communication and ICT impact on educator performance is 0.042 × 0.031 = 0.001302 = 0.1302% This shows that it has a fairly small communication variable influence of 0.1302% on performance As for the Regression equation is: = 0.042 X1 + 0.001 X2 + Error.  (4) The Regression equation is  = 0.042 X1 + 0.001 X2 + ErrorThe research findings show that communication and ICT skills simultaneously (simultaneously) affect the performance of educators, so that the quality of learning is increasing.